Environmental Factors and their Impact on Human Health: Risk Assessment and Disease Prevention - Jurabekovna, Norboeva Gulasal; Khasanovna, Mansurova Malika (American Journal of Bioscience and Clinical Integrity, 2025)
This article examines various environmental factors that affect human health. It discusses the main sources of environmental pollution, the mechanisms of their impact on health, as well as the social, economic, and cultural aspects contributing to these problems. Recommendations are provided to minimize negative health effects and improve the quality of life of the population.